Outcome of SIOP patients with low- or intermediate-risk Wilms tumour relapsing after initial vincristine and actinomycin-D therapy only − the SIOP 93–01 and 2001 protocols. (March 2022) - Groenendijk, Alissa; van Tinteren, Harm; Jiang, Yilin; de Krijger, Ronald R.; Vujanic, Gordan M.; Godzinski, Jan; Rübe, Christian; Schenk, Jens-Peter; Morosi, Carlo; Pritchard-Jones, Kathy; Al-Saadi, Reem; Vaidya, Sucheta J.; et al.
Abstract: Purpose: Society of International Pediatric Oncology – Renal Tumor Study Group (SIOP-RTSG) treatment recommendations for relapsed Wilms tumour (WT) are stratified by the intensity of first-line treatment. To explore the evidence for the treatment of patients relapsing after vincristine and actinomycin-D (VA) treatment for primary WT, we retrospectively evaluated rescue treatment and survival of this patient group. Patients and methods: We included 109 patients with relapse after VA therapy (no radiotherapy) for stage I-II primary low- or intermediate-risk WT from the SIOP 93–01 and SIOP 2001 studies. Univariate Cox regression analysis was performed to study the effect of relapse treatment intensity on event-free survival (EFS) and overall survival (OS). Relapse treatment intensity was classified into vincristine, actinomycin-D, and either doxorubicin or epirubicin (VAD), and more intensive therapies (ifosfamide/carboplatin/etoposide [ICE]/≥ 4 drugs/high-dose chemotherapy with haematopoietic stem cell transplantation [HD HSCT]). Results: Relapse treatment regimens included either VAD, or cyclophosphamide/carboplatin/etoposide/doxorubicin (CyCED), or ICE backbones. Radiotherapy was administered in 62 patients and HD HSCT in 15 patients. Overall, 5-year EFS and OS after relapse were 72.3% (95% confidence interval [CI]: 64.0–81.6%) and 79.3% (95% CI: 71.5–88.0%), respectively. Patients treated with VAD did not fare worse when compared with patients treated with more intensive therapies (hazard ratio EFS: 0.611 [95% CI: 0.228–1.638] [ p -value = 0.327] and hazard ratio OS: 0.438 [95% CI: 0.126–1.700] [ p -value = 0.193]). Conclusion: Patients with relapsed WT after initial VA-only treatment showed no inferior EFS and OS when treated with VAD regimens compared with more intensive rescue regimens. A subset of patients relapsing after VA may benefit from less intensive rescue treatment than ICE/CyCED-based regimens and deserve to be pinpointed by identifying additional (molecular) prognostic factors in future studies. Highlights: On behalf of the Society of International Pediatric Oncology- Renal Tumor Study Group. Risk stratification of relapsed Wilms tumour is based on primary treatment intensity. Patients treated with vincristine and actinomycin-D are advised a four-drug therapy at relapse. A three-drug therapy is adequate relapse treatment in a subset of patients. Identification of this subset requires large-scale epidemiological and molecular studies.